2022
DOI: 10.1186/s13002-022-00559-z
|View full text |Cite|
|
Sign up to set email alerts
|

Incorporating local stakeholders’ voices and knowledge into conservation decisions: a case study on the Chinese Hwamei (Garrulax canorus Linnaeus, 1758) in Taijiang, Guizhou, China

Abstract: Background The Chinese Hwamei (Garrulax canorus Linnaeus, 1758) is a widely distributed species and has long been kept as a pet, especially by the ethnic communities in Southwest China. According to conservation experts’ suggestions, it has been designated as a second-level national key protected species in February, 2021 to protect this bird, indicating that keeping it at home is no longer permitted in China. However, a key factor to ensure effectiveness and success of conservation initiatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Following publication of the original article [ 1 ], the author reported that an incorrect version of Fig. 1 had been provided, in which South China Sea islands had not been presented in the map.…”
Section: Correction To: Journal Of Ethnobiology and Ethnomedicine (20...mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the author reported that an incorrect version of Fig. 1 had been provided, in which South China Sea islands had not been presented in the map.…”
Section: Correction To: Journal Of Ethnobiology and Ethnomedicine (20...mentioning
confidence: 99%